A novel rotated sigmoid weight function for higher performance in heterogeneous deformation measurement with digital image correlation - Ye, Xiaosen; Zhao, Jiaqing (Optics and lasers in engineering, 2022)
•A new rotated sigmoid weight (RSW) function based DIC (RSW-DIC) is proposed to tackle the problem that the results of the weight function based DIC are influenced by the initial subset size (here ‘initial’ means ‘original’, the initial subset size keepsconstant over iterations, but the equivalent subset size is varying according to the weight distribution). The RSW-DIC has much better performance than other weight function based methods for unknown heterogeneous displacement.•The spatial resoltion of the proposed method is much better than other DIC methods using the same subset and shape functionorder.•The proposed RSW-DIC has better noise resistance than other participated methods. The Measurement resolution can be reduced by using a big initial subset size without increasing spatial resolution much. Conventional digital image correlation (C-DIC) combined with a rotated Gaussian weight (RGW) function for subset has demonstrated attractive ability in resolving heterogeneous deformation parameters. To further improve the performance, the selection of an optimum weight function becomes the key issue. In this paper, a novel rotated sigmoid weight (RSW) function is proposed. RSW function aims to get a more uniform weight distribution near the subset center, and to realize the continuous change of the equivalent subset size as well. The performance of the RSW function is compared with the Gaussian weight (GW) function, RGW function, the rotated inverse distance weight (RIDW) function and the inverse distance square weight (RIDSW) function through Star 5 image set from the DIC challenge 2.0 and the simulated image set. A total of six methods with different weight functions and rotated weights are systematically compared. The experiment results clearly show that DIC combined with RSW function (i.e. RSW-DIC) has the best spatial resolution without sacrificing much measurement resolution. The spatial resolution of RSW-DIC is only about half of the other methods for both first- and second-order shape functions when a big initial subset size is adopted.